Stasys Šalkauskis – An Initiator of the Methodology of Scientific Work - Sirtautas, Vytautas (Acta Paedagogica Vilnensia, 1997)
T The article is devoted to revealing the activities of the Lithuanian pedagogue and philosopher Stasys Šalkauskis (1886-1941) in the field of methodology of scientific work. In 1926 he wrote the book “Fundamentals of General Methodics of Research Work” and is the initiator in this sphere. The competence of his work was of world-wide significance at that time. The science is naturally perfecting itself at present; however, the importance of Šalkauskis' works has remained up to present day.
Keywords: philosophy of education; S. Šalkauskis; methodology of scientific work; terminology of pedagogy